Intelligent trading/metering/billing system ITMBS-I-A intelligent meter design - Sutedy, Vincent (2009)
As Singapore is moving towards Clean Energy environment, several implementation and research activities have been ongoing. The Renewable Clean Energy industry comprises a broad range of areas examples solar cells, water power, wind turbine, biogas, geothermal and carbon trading. Singapore aims to grow this industry, generating S$1.7 billion of value-added by 2015. Another key issue is the liberalization of the Singapore Electrical energy market and opening up of Electrical retailing market had bought a new scene in the Singapore energy market. Consumer will be able to enjoy better service and price for the electricity. However the current system tracking of electrical energy consumption is unable to meet the requirements of the new energy market in Singapore.